Exploring textures in enhancing spatial perception for visual impairment people (ARTEKS : Jurnal Teknik Arsitektur, 2025)
EyeSight is one of the important senses for us to keep in touch with our surroundings. People with visual impairment always rely on their sensory perception to interact with spatial environments. Textured surfaces can be used to create a sense of movement. And yet, visual impairment poses significant challenges to spatial perception and navigation. Hence, there remains a gap in understanding the standard exploration of spatial qualities to evaluate the efficiency of textures in enhancing spatial perception. The research methodology involves qualitative methods by researching the case studies and interview sessions with visually impaired people and the staff from the Malaysian Association for the Blind (MAB). Research findings throughout the study highlight the importance of texture characteristics in facilitating spatial perception. It explores the interaction between tactile textures and sensory modalities for visually impaired people. This research aims to investigate the utility of textures in the interior in enhancing spatial perception for visually impaired people. Also, this research explores the application of varied textures to be used in the interior for visually impaired people. The findings are important for determining the best texture for the enhancement of spatial perception for visually impaired people.
Keywords: Spatial perception; Textures; Visually impaired